Проблема профілактики порушень опорно-рухового апарату в дітей молодшого шкільного віку з послабленим зором у процесі фізичного виховання - Сергієнко, Костянтин; Джуха, Хабіб; Sergienko, Konstantin; Juha, Habib (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Представлено аналіз літературних джерел із проблеми профілактики порушень опорно-рухового апарату в молодших школярів із порушенням зору. За даними різних авторів установлено взаємозв'язок між дефектом зорового аналізатора як основної нозології та вторинних відхилень і захворювань опорно-рухового апарату в дітей молодшого шкільного віку з порушенням зору. Подано різні методики, технології, які стосуються проблеми корекції та профілактики опорно-рухового апарату в молодших школярів із порушенням зору в процесі фізичного виховання. The analysis of the literature on the issue of prevention of disorders of the musculoskeletal system in primary school children with visual impairment is presented. According to various authors the interrelation between impairment of the visual analyzer as the main nosology, and secondary abnormalities and diseases of the musculoskeletal system in children of primary school age with visual impairment was set. Despite numerous studies, the problem of musculoskeletal disorders of the foot of spring properties of a test contingent confirms the relevance and need for research.Various techniques and technologies related to the problem of correction and prevention of musculoskeletal in primary school children with visual impairments in physical education were represented.
The Problem of Prevention of Disorders of the Musculoskeletal System at the Primary School Children With Impaired Vision in Physical Education
Keywords: опорно-руховий апарат; профілактика; молодші школярі з ослабленим зором; musculoskeletal system; preventive maintenance; younger students with low vision